The lncRNA Connection Between Cellular Metabolism and Epigenetics in Trained Immunity - Fok, Ezio T.; Davignon, Laurianne; Fanucchi, Stephanie; Mhlanga, Musa M. (Frontiers in Immunology, 2019)
Trained immunity describes the ability of innate immune cells to form immunological memories of prior encounters with pathogens. Recollection of these memories during a secondary encounter manifests a broadly enhanced inflammatory response characterised by the increased transcription of innate immune genes. Despite this phenomenon having been described over a decade ago, our understanding of the molecular mechanisms responsible for this phenotype is still incomplete. Here we present an overview of the molecular events that lead to training. For the first time, we highlight the mechanistic role of a novel class of long non-coding RNAs (lncRNAs) in the establishment and maintenance of discrete, long lasting epigenetic modifications that are causal to the trained immune response. This recent insight fills in significant gaps in our understanding of trained immunity and reveals novel ways to exploit trained immunity for therapeutic purposes.